1985
DOI: 10.1016/0014-5793(85)81080-2
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis of mitochondria in reticulocytes during maturation is ubiquitin‐dependent and is accompanied by a high rate of ATP hydrolysis

Abstract: The ATP-dependent breakdown of mitochondria-containing stroma proceeds via the ubiquitin-requiring pathway. The proteolysis is linked to a large ATP-cleaved consumption amounting to 1 ATP per peptide bond or more. Proteins of mitochondria-containing stroma are much better substrates of ATP-ubiquitindependent proteolysis than heat-denatured ones. Hemin suppresses both proteolysis and ATP hydrolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 18 publications
3
28
0
1
Order By: Relevance
“…Although considerable conjugation occurs at lower pH values, these high pH values are found only in the stroma in the chloroplasts and the mitochondria matrix. Ubiquitin-dependent proteolysis has been described in reticulocyte mitochondria (21), and our results show not only that RuBPCase can undergo ubiquitin-dependent degradation in vitro (Fig. 4), but also the existence ofthe conjugating enzymes in chloroplasts (Figs.…”
Section: Discussionsupporting
confidence: 75%
“…Although considerable conjugation occurs at lower pH values, these high pH values are found only in the stroma in the chloroplasts and the mitochondria matrix. Ubiquitin-dependent proteolysis has been described in reticulocyte mitochondria (21), and our results show not only that RuBPCase can undergo ubiquitin-dependent degradation in vitro (Fig. 4), but also the existence ofthe conjugating enzymes in chloroplasts (Figs.…”
Section: Discussionsupporting
confidence: 75%
“…This effect was equally observed in the case of degradation by the lysosomal extract (as shown) and also with a reticulocyte extract (not shown) which we have tested for comparative purposes, since it contains a very active ATPdependent proteolytic system directed to the destruction of mitochondria during cell maturation [12].…”
Section: Resultssupporting
confidence: 57%
“…In reticulocytes the inhibition of intracellular proteolysis effected a saving equivalent to 1 ATP per peptide bond hydrolysed (Siems et al, 1984;Rapoport et al, 1985). Recently Driscoll and Goldberg (1989) demonstrated that the proteasome (a multicatalytic endoproteinase complex) is activated 4-12-fold by ATP.…”
Section: Protein Turnovermentioning
confidence: 99%